2020
DOI: 10.3389/fevo.2020.00034
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Migration of Rock Ptarmigan in Central Scandinavia

Abstract: In a world undergoing massive declines in the distribution and abundance of many wildlife species, documenting basic ecological characteristics is often needed to be able to understand and potentially mitigate current and future pressures. Species living in alpine areas might be particularly vulnerable to climate change, in part because they are less likely to be able to migrate to new suitable areas. Here we report from a two year case study of rock ptarmigan (Lagopus muta) in central Scandinavia. Ptarmigan w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…During February and March 2015–2019, we captured a total of 188 willow ptarmigan at night using snowmobiles and large hand nets with prolonged handles, as described in Nilsen, Moa, Brøseth, Pedersen, and Hagen (2020). To prevent birds from flying off before the field personnel were close enough to capture them, a high‐powered headlamp was used to dazzle the birds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During February and March 2015–2019, we captured a total of 188 willow ptarmigan at night using snowmobiles and large hand nets with prolonged handles, as described in Nilsen, Moa, Brøseth, Pedersen, and Hagen (2020). To prevent birds from flying off before the field personnel were close enough to capture them, a high‐powered headlamp was used to dazzle the birds.…”
Section: Methodsmentioning
confidence: 99%
“…During February and March 2015-2019, we captured a total of 188 willow ptarmigan at night using snowmobiles and large hand F I G U R E 1 Study area (outlined box) showing all marking locations (red triangles) and telemetry positions (blue dots) of the marked birds. The northern cluster of red triangles represents the Lifjellet location and the southern cluster Gusvatnet nets with prolonged handles, as described in Nilsen, Moa, Brøseth, Pedersen, and Hagen (2020). To prevent birds from flying off before the field personnel were close enough to capture them, a highpowered headlamp was used to dazzle the birds.…”
Section: Field Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that ptarmigans are migratory (Irving et al, 1967;Hoffman & Braun, 1975;Gruys, 1993;Brøseth et al, 2005;Hörnell-Willebrand et al, 2014;Nilsen et al, 2020b). Hörnell-Willebrand et al (2014) reported large individual variation in seasonal migration distances in willow ptarmigans.…”
Section: Prefacementioning
confidence: 99%
“…The highest population density of Oriental skylark was observed in habitats where crops were more diverse; as crop types offer more suitable habitats for nest construction throughout the breeding period [15]. Oriental skylark does not inhabit vegetation more than 30 to 35 cm in height [15,16]. Little data are available on the ecology of Oriental skylark in Pakistan.…”
Section: Introductionmentioning
confidence: 99%